ELABORATING AN INDONESIAN SOCIAL MARIOLOGY BASED ON THE EXPERIENCE OF THE FAITHFUL - Pasi, Gregorius; Riyanto, Armada; Martasudjita, Emanuel P.D. (Journal of Asian Orientation in Theology, 2022)
This article attempts to answer the following question: how to elaborate an Indonesian social mariology that is based on the experience of the faithful? In answering this question, this article uses the critical reading method on four main themes, namely: (1) social mariology according to Clodovis M. Boff; (2) Contextual theology according to the FABC (Federation of Asian Bishops' Conferences); (3) The methods of contextual theology according to Stephen B. Bevans; (4) Gadamer's philosophical hermeneutics. The results of this critical reading have been synthesized in the following 3 subjects: (1) social mariology, (2) social mariology within the context of the FABC’s contextual theology; (3) a plan of Indonesian social mariology based on the experience of the faithful. An authentic contribution of this article is found in number 3: it offers a way to be applied in heeding the context, namely by processing the experience of the faithful. This approach is based on the way of Asian contextual theologizing according to the FABC and Gadamer's philosophical hermeneutics. Besides to social mariology, this method can be applied to other themes of contextual theological studies.